Non-Q-Wave Myocardial Infarction: Comprehensive Analysis of Electrocardiogram and Pathological Correlation - Velasco, Manuel; Rojas, Edward (Síndrome Cardiometabólico y Enfermedades Crónico Degenerativas, 2012)
Non–Q-Wave Myocardial Infarction (NQwMI) has been defined as an Acute Myocardial Infarction (AMI) without a new onset deep Q wave on the Electrocardiogram (ECG) after day/days of evolution. Correlations between pathophysiology and ECG findings in the NQwMI not yet well understood and the culprit lesion after NQwMI has not been well characterized. Also, there is no consensus according to the clinical usefulness of the Qw and NQw Myocardial infarction definition. The anatomopathological concept of infarction is usually related to necrosis and it results paradoxical to consider this widely known clinical entity as a myocardial infarction when absence of ECG evidence of necrosis is observed. One of the proposed explanations to this ECG phenomenon is that in fact there is an important coronary obstruction that compromises myocardial viability but its natural history is modified by endogenousmechanisms such as tissue plasminogen activator,oxygen reactive species diminishment via superoxide dismutase, cessation of vasospasm through adenosine production and other molecular mechanisms happening before two hours of initiated the coronary flow obstruction.These are is the main discussion topics in this review article aiming to clarify why a NQwMI is in fact considered an infarction of myocardial tissue without ECG evidence of inert myocardium not capable to depolarize and if its clinical differentiation with Untable Angina represents further therapeutic implications or not.